Implementation of the STAD Type Cooperative Learning Model with Gimkit to Improve Student Learning Outcomes on Substances and Their Changes - Adinda, Nefitri; Azhar, Azhar; Nasir, Muhammad (Journal of Educational Sciences, 2025)
In the implementation of evaluation is usually done by paper test method. By utilizing technological developments, the implementation of learning evaluation can take place more optimally. This study aims to describe the improvement of students' cognitive learning outcomes and determine significant differences in students' cognitive learning outcomes through the application of the STAD cooperative learning model assisted by Gimkit and the STAD cooperative learning model without Gimkit on the material of substances and their changes. The research method used is a quasi-experiment with a post-test-only control design. The data collection technique is a post-test. The results of the descriptive analysis in the experimental class obtained an average cognitive learning outcome of 81.45 in the very good category. While in the control class obtained an average score of 66.38 in the good category. The results of the hypothesis test obtained 0.002 which is smaller than 0.05 which means there is a significant difference in the cognitive learning outcomes of students who apply the STAD cooperative learning model assisted by Gimkit with those who apply the STAD cooperative learning type alone on the material of substances and their changes in class VII SMP Islam Ash-Shofa Pekanbaru.